Determinants of Smoking Behavior Among Indonesian Men: Evidence from the 2017 Indonesian Demographic and Health Survey - Habib Adwi Prasetyo; Yuni Asri; Riki Ristanto (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: Smoking remains a major public health problem in Indonesia, particularly among males, and contributes substantially to morbidity and mortality. Sociodemographic inequality, socioeconomic status, and environmental factors may influence smoking behavior among Indonesian men; however, nationally representative evidence remains limited. Objective: This study aimed to analyze factors associated with smoking behavior among male respondents in Indonesia. Methods: This study employed a cross-sectional design using secondary data from the Indonesian Demographic and Health Survey (IDHS) 2017 male recode dataset (IDMR71FL). A total of 9,945 male respondents were included in the analysis. Sampling weights were applied to account for the complex survey design. The dependent variable was smoking behavior, while independent variables included age, education level, occupation, wealth index, residence, province, newspaper reading, television watching, radio listening, and internet use. Data were analyzed using IBM SPSS Statistics version 27.0.1. Descriptive statistics, chi-square tests, and multivariable logistic regression were performed with a significance level of p<0.05. Results: Education level, wealth index, residence, and province were significantly associated with smoking behavior. Respondents with junior high school education were more likely to smoke (AOR=1.57; 95% CI: 1.13–2.19), whereas respondents with academy or university education showed lower odds of smoking behavior (AOR=0.57; 95% CI: 0.39–0.82). High-income respondents had lower odds of smoking compared with low-income respondents (AOR=0.68; 95% CI: 0.61–0.77). Rural residence was associated with higher smoking behavior (AOR=1.16; 95% CI: 1.04–1.28). Conclusion: Smoking behavior among Indonesian males was significantly influenced by educational attainment, socioeconomic status, residence, and regional characteristics. Strengthening tobacco control interventions targeting vulnerable male populations is necessary to reduce smoking prevalence in Indonesia.